Health status of University students in the light of the research carried out in Poland in years 1970-2010 - Bracław, Marzena; Górniak, Krystyna (Polish Journal of Public Health, 2011)
Introduction. Health is one of the primary rights of humans and, as evidenced in the “National Health Programme for 2007–2015”, the key human ally in the pursuit of selffulfilment, success at work, personal happiness and the satisfying performance of the social roles, as well as a good adaptability to any environmental changes.Aim. The present article is an attempt to describe the health status of the Polish university students studying In years 1970-2010 .The choice of such a wide period of time covering nearly 40 years was dictated by the willingness to indicate the changes that have occurred in the area of interest covered in this article.Material and Methods. The study contains the comparison introduced in the literature on the subject analysis of findings in years 1970-2010. The subject of the article is presented from two different perspectives: as the respondents’ subjective assessment and in the light of the results provided by the objective medical research.Results. The increase in the disease incidence rate observed among the university students at the end of the 1970s was related to diseases such as mental disorders and diseases of the respiratory, digestive, and nervous systems, as well as disorders of the sense organs. The diseases that are observed most frequently today are orthopaedic impairments, disorders of the motor organs, postural defects and abnormal spinal curvature, diseases of the blood circulation and respiratory systems, diabetes, and growing mental disorders. Forty per cent of the students qualify for the groups of patients with chronic conditions.Conclusions. In Poland a large deterioration of health In young people has been observed. The analysis of the Young Poles’ condition presented in this study points to the necessity of not only raising their awareness of the existing hazards, but also forming the proper habits, manners and conduct In young students as they approach adulthood. It is also import ant that they should constantly improve their knowledge on how to prevent various illnesses